Creep characteristics of austenitic stainless steel foils under oxidative and non-oxidative environment - Fatimah Mohammed Kadhim (2015)
Compact and high efficiency recuperator with thin foil corrugated air cell as the primary surface is employed in clean and efficient microturbine system (100 kW). Current primary surface recuperators are made of AISI 347 austenitic stainless steel foils that operate at gas inlet temperature of less than 650 °C and attain approximately 30 percent of efficiency. Efficiency of greater than 40 percent is possible with the increase in turbine inlet temperature to 1230 °C, and as a result recuperator inlet temperature increase to 843 °C. This study establishes base line creep rupture behaviour of AISI 347 austenitic stainless steel foils at operating temperature of 700 °C and applied stresses of 150,182 and 221 MPa in air as oxidation environment, and in inert gas (Argon gas) as non-oxidation environment. Creep behaviour of the foil shows that the primary creep stage is short and creep life of the foil is dominated by secondary and tertiary creep deformation. The time to rupture for the foil specimen is 78 hours with the corresponding rupture strain of 18.42 percent in air and 102 hours with the corresponding rupture strain of 15 percent in Argon gas for the applied stresses of 150,182 and 221 MPa at 700 °C. Creep curves for AISI 347 austenitic stainless steel foil at 700 °C and at 150,182 and 221 MPa are well represented by the modified Theta-Projection concept model with hardening and softening terms. The creep coefficients, ?1 and ?3, and the exponent a are 0.0355, 0.04645 and 1.39 respectively in air and 0.0035, 0.048 and 1.3 respectively in Ar gas environment. Theta-Projection parameter values of the creep curves at temperature of 700 °C and applied stress of range 150,182 and 221 MPa shows a sudden gradient change at applied stress of 150 MPa possibly due to different mechanism of dislocation movements and microstructure changes. the creep curves for AISI 347 austenitic stainless steel foil at 700 °C and at 150,182 and 221 MPa in inert gas are represented by the power-law model and parameters of this model A, n and Q are 7.947(1010), 1.73 and 556.4KJ/mol., respectively. Two different creep failure mechanisms for austenitic stainless steel foils are possible since the creep failure data falls very close to the boundary of dislocation and diffusion creep regions in the creep mechanism map for bulk material.morphology of fractured foil surface revealed intergranular fracture with shallow network of faceted voids. The formation of creep cavities is significant. Post test phase analysis indicates the formation of carbides, namely Cr23C6, NbC and Fe3Nb3 C.